Formulation of Fenugreek-Based Nutritional Jelly to Enhance Paediatric Appetite - Pagar Purvesh; Bhalke Rasika; Gangurde Shreya; Kangane Yash; Pagare Tejsvini; Giri Mahendra; Jadhav Hemangi (Asian Journal of Pharmaceutical Research and Development, 2026)
This study aimed to create and assess a natural jelly for children that stimulates appetite. It used fenugreek and beetroot, along with cinnamon and rosemary. Fenugreek helped boost appetite, while beetroot improved taste, colour, and nutritional value. Cinnamon and rosemary added antioxidant, antimicrobial, and stabilizing properties. The formulation was adjusted for taste, stability, and effectiveness. The evaluation included checking physical and chemical properties, ensuring microbial safety, conducting sensory analysis, and performing in vivo appetite tests. The results showed good taste and safety, with a potential increase in appetite among children The evaluation results showed that F2 formulation was optimal with pH 6.8, best texture (310 g), lowest moisture content (27.0 ± 0.25%), light brown colour, and highest viscosity (5400 cP), indicating better stability, consistency, and overall acceptability compared to F1 and F3. The study concludes that this herbal jelly is a promising, safe, and appealing appetite stimulant with added health benefits.